2019
DOI: 10.1007/s00784-019-03097-3
|View full text |Cite
|
Sign up to set email alerts
|

Virtual setup in orthodontics: planning and evaluation

Abstract: Objectives The purpose of this study was to evaluate the clinical accuracy of virtual orthodontic setups by using a new CBCTbased approach. Materials and methods Ten patients who underwent pre-surgical orthodontics were included in this study. Pre-treatment and presurgical cone-beam CT (CBCT) scans and digital dental models were available. The pre-treatment digital dental model was used to create an orthodontic virtual setup. The digital dental models were fused with the corresponding CBCT scans, and the two C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Measuring the individual teeth movement was a process which has a low variability (ICC > 0.70). These findings are in line with an earlier study which describes the use of surfacebased superimposition in individual teeth movement [34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Measuring the individual teeth movement was a process which has a low variability (ICC > 0.70). These findings are in line with an earlier study which describes the use of surfacebased superimposition in individual teeth movement [34].…”
Section: Discussionsupporting
confidence: 93%
“…All scans and individually segmented teeth were then imported into custom made software (3DMedX) that was developed with C++ in Microsoft Visual Studio 2015 ((version 14.0) Microsoft Corporation, Redmond, WA, USA) [33]. This easy-to-use software moved the segmented teeth from the imported T0 scan to the position of the teeth within the scans taken at later time points using surface-based registration as described by Baan et al [34]. Clinically relevant information, such as anterior/posterior, left/right and up/down movements were given as output by the software.…”
Section: Collection and Superimposition Of 3d Scansmentioning
confidence: 99%
“…Another limitation of this study is the choice for the explorative design because of the limited amount of available literature and the use of a relatively new 3D method to follow tooth movements in 3D [ 12 ]. This may complicate the judgment of the results in a clinical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of a new method for integrating digital setups into CBCT scans, orthodontic setups can be integrated into the virtual orthognathic planning. Instead of being fabricated just before the surgery, all of the planning can now be mapped out ahead of orthodontic treatment initiation [ 12 ]. A study by Falter et al [ 13 ] revealed that one in seven orthognathic patients (13.5%) underwent a different surgical procedure from that originally planned mainly because of facial aesthetic considerations or a negative overjet that did not change as expected in Class III patients.…”
Section: Introductionmentioning
confidence: 99%
“…In all, those who cannot tolerate pain or have aesthetic needs [ 6 , 9 , 11 , 19 , 20 ]. Additionally, multidisciplinary pre-prosthetic or pre-surgical treatments can benefit from the use of aligners [ 19 , 21 ]. Patient collaboration is an essential element to the success of the treatment [ 9 , 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%